y = ln(4x/5-3x)
What I have done is -
ln4x - ln(5-3x)
= dy/dx = 1/4x - 1/(5-3x)
= (5-3x-4x)/4x(5-3x)
Which is the wrong answer, please help?
I hope I have posted this in the right place, my apologies if not?
y = ln(4x/5-3x)
What I have done is -
ln4x - ln(5-3x)
= dy/dx = 1/4x - 1/(5-3x)
= (5-3x-4x)/4x(5-3x)
Which is the wrong answer, please help?
I hope I have posted this in the right place, my apologies if not?
U have to use the chain rule, because you're dealing with composite functions:
You're first step is good. But then it went wrong, because you didn't use the chain rule:
If you want to calculate for example:
Let
so you get:
Use also the chainrule to calculate or notice that